ANALISIS PUTUSAN PENGADILAN TATA USAHA NEGARA NOMOR 3/G/2022/PTUN/KUPANG TENTANG PENGANGKATAN KEPALA DUSUN 1 DI DESA TANAH MERAH KABUPATEN KUPANG - Liong, Hironimus; Yohanes, Saryono; Ratu Udju, Hernimus (Petitum Law Journal, 2023)
The village already has an established institutional structure that is respected and preserved by the village community . Village officials carry out public services that have duties and responsibilities towards serving the community, and assisting the Village Head in carrying out their duties. Village apparatus, in this case the Head of Hamlet I filed a lawsuit against the Head of Tanah Merah Village, that the Head of Hamlet I Meryati Astriana Djami was unilaterally aborted by the Village Head in Tanah Merah Village, Kupang Tengah District, to the Kupang State Administrative Court. Then the main problem can be formulated: (1) What is the mechanism for selecting and appointing hamlet heads in Kupang Regency based on laws and regulations? (2) What is the basis for the judge's consideration of the dismissal of the Candidate for Hamlet Head I of Tanah Merah Village, Kupang Regency based on Law Number 6 of 2014 concerning Villages? This research is a normative juridical research because it was conceptualized and developed by examining the rules, norms, rules related to the problem under study. The research results show that: (1) The mechanism for selecting and appointing hamlet heads in Kupang Regency is carried out based on Kupang Regent Regulation Number 5 of 2021 concerning Procedures for Appointing and Inaugurating Village Officials . (2) panel of judges No foundit error procedure in accordance with mandate the law Law on Government Administration as amended by Law Law Number 11 of 2020 concerning Job Creation . Therefore, suggestions regarding the results of this study are: (1) The mechanism for selecting and appointing hamlet heads in Kupang Regency needsto be socialized comprehensively to the entire election team. (2) The need for a family approach in solving this problem.